Microarray genomotyping of key experimental strains of Neisseria gonorrhoeae reveals gene complement diversity and five new neisserial genes associated with Minimal Mobile Elements. - Saunders Nigel J; Davies John K; Snyder Lori AS (BMC Genomics, 2004)
Abstract Background There are four widely used experimental strains of N. gonorrhoeae, one of which has been sequenced and used as the basis for the construction of a multi-strain, mutli-species pan-neisserial microarray. Although the N. gonorrhoeae population structure is thought to be less diverse than N. meningitidis, there are some recognized gene-complement differences between strains, including the 59 genes of the Gonococcal Genetic Island. In this study we have investigated the three experimental strains that have not been sequenced to determine the extent and nature of their similarities and differences. Results Using the Pan-Neisseria microarray, three commonly used gonococcal laboratory experimental strains were investigated (F62, MS11, & FA19). Genes absent from these strains, but present in strain FA1090, were assessed as is possible with typical microarrays. Due to the design of this microarray, additional genes were also identified. Differences were associated with Minimal Mobile Elements (MMEs) or known divergences. Genomotyping indicates the presence of genes previously only described in meningococci and shows the presence of the complete Gonococcal Genetic Island in N. gonorrhoeae strain FA19. Five new neisserial genes were identified through microarray genomotyping and subsequent sequencing of two divergent MMEs in N. gonorrhoeae strain MS11 and four MMEs in N. gonorrhoeae strain FA19. No differences were identified between N. gonorrhoeae strains FA1090 and F62, indicating that these strains are very similar. Conclusion This study shows extensive similarity between the experimental strains, associated with a varying number of strain-specific genes. This provides a framework for those working with these strains to refer to the available gonococcal genome sequence, and is the first detailed comparison of gene complements between gonococcal strains.